Complex neurodevelopmental disorder in a preterm child with unilateral cerebellar hemorrhage. Issue 4 (2nd October 2022) - Bonaventura, Eleonora; Purpura, Giulia; Pasquariello, Rosa; Da Prato, Sara; Di Lieto, Maria Chiara; Barsotti, Jessica; Paolicelli, Paola Bruna; Cioni, Giovanni; Tinelli, Francesca
Abstract: Background: Cerebellar hemorrhage (CBH) represents the main form of direct cerebellar injury in preterm infants. Most CBHs occur bilaterally, while isolated unilateral hemorrhages are less frequent and often associated with focal atrophy. Limited and heterogeneous data exist on preterm birth, unilateral CBH and consequent long-term neurodevelopmental and non-motor outcomes. Case report: This is the case of a six-year-old child, born preterm, diagnosed with a complete atrophy of the right cerebellar hemisphere through brain MRI and presenting mild social atypies, visuo-perceptive and pragmatic language impairment, but only minor neurological signs. Discussion: Despite the large extension of the patient's CBH neurological sequelae were mild, likely due to cerebellar plasticity, and only specific deficits in non-motor, behavioral and social skills were shown. Evidence exists on cerebellar contribution to dynamic visual information processing and to perceptual signals detection and prediction, that might explain the presence of non-motor signs.